2018
DOI: 10.15252/embr.201845942
|View full text |Cite
|
Sign up to set email alerts
|

The dual role of the centrosome in organizing the microtubule network in interphase

Abstract: Here, we address the regulation of microtubule nucleation during interphase by genetically ablating one, or two, of three major mammalian γ-TuRC-binding factors namely pericentrin, CDK5Rap2, and AKAP450. Unexpectedly, we find that while all of them participate in microtubule nucleation at the Golgi apparatus, they only modestly contribute at the centrosome where CEP192 has a more predominant function. We also show that inhibiting microtubule nucleation at the Golgi does not affect centrosomal activity, whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 57 publications
9
59
0
Order By: Relevance
“…Even if the latter is the case, the results indicate that a PCM1‐dependent pool of these factors exists within close proximity of centrosomes. We also noted a previously unreported decrease in γ‐tubulin levels in PCM1‐KO clones, especially during interphase (Fig C), which may be a secondary consequence of reduced centrosomal levels of pericentrin involved in centrosomal recruitment of γ‐tubulin (Lin et al , ; Gavilan et al , ).…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Even if the latter is the case, the results indicate that a PCM1‐dependent pool of these factors exists within close proximity of centrosomes. We also noted a previously unreported decrease in γ‐tubulin levels in PCM1‐KO clones, especially during interphase (Fig C), which may be a secondary consequence of reduced centrosomal levels of pericentrin involved in centrosomal recruitment of γ‐tubulin (Lin et al , ; Gavilan et al , ).…”
Section: Resultssupporting
confidence: 71%
“…Even if the latter is the case, the results indicate that a PCM1-dependent pool of these factors exists within close proximity of centrosomes. We also noted a previously unreported decrease in c-tubulin levels in PCM1-KO clones, especially during interphase (Fig 7C), which may be a secondary consequence of reduced centrosomal levels of pericentrin involved in centrosomal recruitment of c-tubulin (Lin et al, 2015;Gavilan et al, 2018). In summary, the concomitant increase in MIB1 (suppressor of cilia formation) and reduction in SSX2IP (activator of ciliogenesis) could collude to block ciliogenesis in PCM1-KO RPE-1 cells, but effects of PCM1 loss on proliferation ( Fig EV5D), microtubule organisation and centrosomal targeting of proteins may also contribute to the overall phenotype.…”
Section: The Role Of Pcm1 In Steady-state Expression and Localisationsupporting
confidence: 69%
“…Ultrastructural analysis is required to determine if the regenerated MTs are associating with some membranous or cytoskeletal structures. On the other hand, cytoplasmic MT nucleation has been reported in plant cells (Nakaoka, Kimura, Tani, & Goshima, ), and in mammalian cells under nonphysiological conditions where MT nucleation from the centrosome and the Golgi apparatus are both inhibited (Gavilan et al, ). The mechanisms of activation of free γ‐TuRCs in these studies are still unknown.…”
Section: Resultsmentioning
confidence: 99%
“…Since the sequential formation of halos was proposed to be due to their sequential generation from the daughter centriole 8 , we then analyzed their origin in absence of centrosomal centrioles. Resident centriole depletion by centrinone in human interphase cells has been shown to involve microtubule organization from the Golgi apparatus or from multiple cytoplasmic foci 22,23 . In MCC progenitors, the existence of a focal Cen2GFP cloud, from where the halos arose (Fig 4a, supplementary movie 2), suggested that a single acentriolar MTOC was self-organizing in the absence of resident centrioles.…”
Section: Centrosomal Centriole-depleted Cells Form Procentrioles Withmentioning
confidence: 99%